PENINGKATAN PERTUMBUHAN MISELIUM JAMUR TIRAM (Pleurotus ostreatus) YANG DIPENGARUHI OLEH PROMOL 12 - Saat Egra; Muhammad Soesilo Dermawan; Etty Wahyuni; Eko Hary Pudjiwati; Amarullah Amarullah; Dwi Santoso; Deny Murdianto; Sudirman Sirait; Hendris Hendris (ULIN: Jurnal Hutan Tropis, 2019)
White oyster mushroom (Pleurotus ostreatus) is a mushroom that has a variety of basidiomycetes that grow in tropical forests with high humidity. This mushroom is classified as edible, has even been cultivated for a long time by the community. Therefore, nowadays oyster mushrooms have a high value, it caused many people have cultivated these mushrooms. In this study we want to show a difference in the growth of the white oyster mushroom mycelium before given promol 12 (as control) and after being given 12 types of local microbial probiotics (PROMOL12). The method used is RAK (Design random groups). In this study, it was shown that the influence of the growth of white oyster mushroom mycelium was given PROMOL12. The growth of oyster mushrooms showed a difference for baglog 12 promol medium having an average growth of 0.6 cm and a growth period of 14 days, on the other hand baglog media control had an average growth of 0.7 cm with a growth period of 17 days. With the same environmental conditions, the average temperature is 27-29.5OC and the humidity is also not less than 60%, which has an average of 70% -81% which is in accordance with the growth of oyster mushroom mycelium.